Mechanical Strength Of Dissimilar AA7075 and AA6061 Aluminum Alloys Using Friction Stir Welding - N. A. A., Sathari; A. R., Razali; M., Ishak; L. H., Shah (Universiti Malaysia Pahang, 2015)
The present study focuses on the effects of material position and tool rotational speed on the tensile strength of dissimilar AA7071 and AA6061 welded aluminum alloys with a thickness of 2.0 mm in using a conventional milling machine. Ten joints were produced by varying tool rotational speeds and by changing the fixed position of the material on the advancing and retreating sides. The results show that the maximum tensile strength of 207 MPa was achieved for Sample E when AA6061 aluminum alloys were placed on the advancing side at a rotational speed of 1000 rpm with seamless surface appearance and no inner defect across the weld area, while the lowest tensile strength of 160 MPa was obtained for Sample F when AA6061 was placed on the retreating side with severe tunnel defects across the weld area contributing to crack propagation. Thus, in dissimilar welding, weaker materials should be placed on the advancing side to trigger heat from the tool rotation and smooth the material flow formation in the stirred zone.